The effect of vaginal cream containing ginger in users of clotrimazole vaginal cream on vaginal candidiasis - Sheida Shabanian; Sima Khalili; Zahra Lorigooini; Afsaneh Malekpour; Saeid Heidari-Soureshjani (Wolters Kluwer Medknow Publications, 2017)
Vulvovaginal candidiasis is one of the most common infections of the genital tract in women that causes many complications. Therefore, we examined the clinical effect of ginger cream along with clotrimazole compared to vaginal clotrimazole alone in this study. This double-blind clinical trial was conducted on 67 women admitted to the Gynecology Clinic of Hajar Hospital with vaginal candidiasis. The patients were divided randomly into two groups of 33 and 34 people. The diagnosis was made according to clinical symptoms, wet smear, and culture. Ginger-clotrimazole vaginal cream 1% and clotrimazole vaginal cream 1% were administered to groups 1 and 2, respectively, once a day for 7 days and therapeutic effects and symptoms were evaluated in readmission. Data analysis was performed using SPSS version 22, t-test and Chi-square. The mean value of variables itching (P > 0.05), burning (P > 0.05), and cheesy secretion (P < 0.05) in users of ginger-clotrimazole was less than the other group after the treatment. Recurrence in clotrimazole group was 48.5% and in ginger-clotrimazole group 51.2% during the 1-month follow-up with no significant difference. Study results showed that cream containing ginger and clotrimazole 1% was more effective and may be more useful than the clotrimazole to treat vaginal candidiasis.